Identification and Strategies For Strengthening The Planning Capacity of Prabumulih City Potential Tourism Area - Novita Wulandari; Akhmad Muftizar; Bachtari Alam Hidayat; Lies Nur Intan (Dinasti Publisher, 2024)
Inappropriate planning and not in accordance with the potential, the existing conditions will greatly affect the sustainability of a program, activity or development. This study aims to: (1) identify potential tourist areas that can be developed immediately in the short term, and (2) prepare a strategy for strengthening planning capacity oriented to